Consumption desire among children (from 7 to 11): Role of the exposure to social media advertisements and product familiarity - Kawther Methlouthi; Ayoub Nefzi (Cogent Business & Management, 2023)
This paper aims to investigate the origins and outcomes of consumer desires in children, with a specific focus on the role of individual attributes (such as age, gender, and susceptibility to peer influence), desire traits (including content and intensity), exposure to social media ads, and familiarity with desired items. This study applies a combination of qualitative and quantitative approaches. First, multi-method qualitative study was used to explore the experience of consumption desire among children (collage exercise, focus groups with children and informal surveys with the parents of interviewed children). Subsequently, we conducted an experimental study, surveying 267 school children (aged 7 to 11), to empirically examine how personal and desire traits influence their emotional responses and overall life satisfaction. The results strongly underscore the significant impact of child-specific attributes (age, gender, and peer influence) and desire caracteristics (content and intensity) on consequences generated by the experience of consumption desire among children. Furthermore, our research conclusively affirms the pivotal role of peer influence, familiarity with desired products, and exposure to social media ads in shaping the personal desires of children aged 7 to 11.
Keywords: 650; advertising; attitude; children; consumption; desire; emotional reaction; familiarity; social media